Lim               ae^x+be^-x
x tends to ∞  ce^x+de^-x
taking common e^x from nominator as well denominator
lim                e^x(a+be^-2x)
x tends to∞    e^x(c+de^-2x)
Apply limit
a+be^-∞          ⇒a/c    ( e^∞=0 )
kaushik tum kis class me padte ho

This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
 \lim_{x \to \infty} \frac{a\ e^x+ b\ e^{-x}}{c\ e^x + d\ e^{-x}}\\\\= \lim_{x \to \infty} \frac{e^x(a+ b\ e^{-2x})}{e^x(c + d\ e^{-2x})}\\\\= \lim_{x \to \infty} \frac{a+ b\ e^{-2x}}{c + d\ e^{-2x}}\\\\=\lim_{x \to \infty} \frac{a+ b\ 0}{c + d\ 0},=\frac{a}{c}\\\\ as\ lim_{x \to \infty}\ e^{-2x}}\\=as\ lim_{x \to \infty}\ \frac{1}{e^{2x}}}\\=\frac{1}{\infty}=0
1 5 1